PERANCANGAN SISTEM INFORMASI PENGELOLAAN KEUANGAN SEKOLAH BERBASIS WEB DAN SMS GATEWAY DI SMK JAYABEKA 02 KARAWANG - Apit Priatna; Arif Maulana Yusuf (INTECH, 2021)
SMK Jayabeka 02 is a private school located in the Karawang area, which has 4 expertise programs, namely mechanical engineering, light vehicle automotive engineering, office administration and computer network engineering. School financial management still uses Microsoft Excel which requires accuracy in managing and recording, then the data processing process requires a lot of time and energy if the data is already queuing a lot. The purpose of this study is to facilitate the administrative transactions of school payments and expenses as well as to produce accurate data and increase the confidence of parents in students and schools. The method used is observation, interviews and literature study to obtain the required data and use SDLC for the system development model described by the waterfall. With the creation of the system, it is hoped that it can further facilitate every existing process and can improve the quality and trust of parents of students towards students and the school.